Relationship between Corticospinal Excitability While Gazing at the Mirror and Motor Imagery Ability - Jun Iwanami; Hitoshi Mutai; Akira Sagari; Masaaki Sato; Masayoshi Kobayashi (Brain Sciences, 2023)
Mirror therapy (MT) helps stroke survivors recover motor function. Previous studies have reported that an individual’s motor imagery ability is related to the areas of brain activity during motor imagery and the effectiveness of motor imagery training. However, the relationship between MT and motor imagery ability and between corticospinal tract excitability during mirror gazing, an important component of MT, and motor imagery ability is unclear. This study determined whether the motor-evoked potential (MEP) amplitude while gazing at the mirror relates to participants’ motor imagery abilities. Twenty-four healthy right-handed adults (seven males) were recruited. Transcranial magnetic stimulation was performed while gazing at the mirror, and MEP of the first dorsal interosseous muscle of the right hand were measured. Motor imagery ability was measured using the Kinesthetic and Visual Imagery Questionnaire (KVIQ), which assesses the vividness of motor imagery ability. Additionally, a mental chronometry (MC) task was used to assess time aspects. The results showed a significant moderate correlation between changes in MEP amplitude values while gazing at the mirror, as compared with resting conditions, and assessment scores of KVIQ. This study shows that corticospinal excitability because of mirror gazing may be related to the vividness of motor imagery ability.